2018
DOI: 10.1108/compel-01-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid simulation approaches for induction machine calculation

Abstract: Purpose Induction machines for traction applications are operated at working points of high ferromagnetic saturation. Depending on the working point, a broad spectrum of harmonic frequencies appears in the magnetic flux density of induction machines. Detailed loss analysis therefore requires local and temporal highly resolved nonlinear field computation. This loss analysis can be performed in the post processing of nonlinear transient finite element simulations of the magnetic circuit. However, it takes a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…For the computation of the T-FEM, an in-house state-of-the-art Finite Element (FE) solver called iMOOSE/pyMOOSE [47] is used. To reduce the computational effort of the T-FEM, a hybrid simulation approach presented in [48] is applied.…”
Section: Electromagnetic Machine Modelsmentioning
confidence: 99%
“…For the computation of the T-FEM, an in-house state-of-the-art Finite Element (FE) solver called iMOOSE/pyMOOSE [47] is used. To reduce the computational effort of the T-FEM, a hybrid simulation approach presented in [48] is applied.…”
Section: Electromagnetic Machine Modelsmentioning
confidence: 99%
“…This, in combination with the required transient time of the vector potential solution, leads to a high calculation effort of the transient Finite Element (FE) simulation. Faster transient is made possible by a hybrid approach via estimation of a starting solution from an open-circuit simulation [20].…”
Section: Transient Finite Element Modelmentioning
confidence: 99%
“…In addition, the magnetic flux distribution is visualised [23]. In the case of the IM, this type of simulation is also used to extract the lumped parameter matrices that are necessary for the hybrid simulation scheme described in [24] and the next section. The demagnetisation test is used for permanent magnet (PM) machines.…”
Section: Operating Point Simulationmentioning
confidence: 99%
“…In the linear and non-linear hybrid FEA, transient and static FE simulations are coupled with analytic models resulting in a hybrid simulation scheme. In [24] it is shown that those approaches reduce the simulation time of the IM, especially of the rotor flux development drastically. One requirement for this hybrid simulation scheme is the extraction of the lumped parameter matrices L and R describing the inductances and resistances described in [34].…”
Section: Efficiency Map Simulationmentioning
confidence: 99%
See 1 more Smart Citation